Chemical Constituents of Vitex ovata (Verbenaceae) - Ramli, Irmawati; Hamzah, Ahmad Sazali; Aimi, Norio; Lajis, Md Nordin (Universiti Putra Malaysia Press, 1997)
Three compounds, luteolin, ursolic acid and meta-hydroxybenzoic acid were isolated from the leaves of Vitex ovata. The structures of the compounds were identified using modern spectroscopic techniques.